Persepsi Owner Butik Intan Galeri Kebaya dan Fashion House Nelly Memosa Terhadap Kompetensi Mahasiswa Praktek Industri - Wahyu Eka Priana Sukmawaty; Jumariah Ria (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
This study aims to determine the perception of the owner of The Intan Gallery Kebaya Boutique and Fashion House, Nelly Memosa, towards the Competence of Industrial Practice Students. This research method is a qualitative method with a case study approach model. In this study, data collection techniques used interview, observation and documentation methods. Interviews were conducted in-depth with the owner of Intan Gallery Kebaya Boutique, namely Mr Zam Warir and The Owner of Fashion House Nelly Memosa, namely Mrs Gusri Nelly. Observations were made on student activities during pre-employment. In addition, documentation is carried out to photograph student activities and document student activity reports and assessment results from the industry. Data analysis used in this study is data reduction, data presentation and conclusion drawing. The result of this study is that the perception of the owner of Intan Gallery Kebaya Boutique, and Fashion House Nelly Memosa, towards the competence possessed by pre-employment students is good. This can be seen from the skills possessed by pre-employment students, which include designing skills, making patterns, cutting materials, sewing, and finishing. In addition, the skills possessed by pre-employment students are also by the Intan Gallery Kebaya Boutique and Nelly Memosa Fashion House, so implementing pre-employment is beneficial for the business world. The pre-employment program's performance benefits The Diamond Boutique of Galeri Kebaya and Fashion House Nelly Memosa. It is beneficial for production activities in the business world.